Characterization of Women in Kazakh Music Culture - Autolkyn Toktagon (GoAcademica Research & Publishing, 2019)
This article discusses the role of women in traditional musical culture in Kazakhstan and addresses the life and creativity of Dina Nurpeisova (1861-1955). Dina was a respected stupid player, student of the famous kyushi [ii] Qurmanghazy and of a super kyuishi. The article examines Dina's life based on archives that became available only after Kazakhstan became independent. From the 1940s to the 1990s, the Soviet media ended the oppressive conditions of the Kazakh women's revolution. He claimed that women in the